The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1111/j.1528-1157.1997.tb01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Three Patterns of Catamenial Epilepsy

Abstract: Summary:Purpose: On the basis of the neuroactive properties of estradiol and progesterone and the menstrually related cyclic variations of their serum concentrations, we propose the existence of three hormonally based patterns of seizure exacerbation. Because previous reports both support and refute the concept of catamenial epilepsy, we test the hypothesis by charting seizures and menses and measuring midluteal serum progesterone levels to estimate the frequency of epileptic women with catamenial seizure exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
447
2
10

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(485 citation statements)
references
References 41 publications
26
447
2
10
Order By: Relevance
“…It is known that sex hormones and their metabolites can modulate the GABA-receptor complex (GRC) (38). For example, estradiol is known to inhibit GABA and to promote kindling (39) and the occurrence of seizures in both experimental and clinical settings (40). In contrast, progesterone reduces neuronal metabolism, suppresses kindling and epileptiform discharges, and decreases the occurrence of seizures (2,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that sex hormones and their metabolites can modulate the GABA-receptor complex (GRC) (38). For example, estradiol is known to inhibit GABA and to promote kindling (39) and the occurrence of seizures in both experimental and clinical settings (40). In contrast, progesterone reduces neuronal metabolism, suppresses kindling and epileptiform discharges, and decreases the occurrence of seizures (2,(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been suggested that women with epilepsy, who have an increase in seizures during the periovulatory period of their menstrual cycle (Catamenial Epilepsy, Type I; [147]) might do so because of the rapid rise in estradiol before ovulation. It is also possible, although less commonly discussed, that seizures that occur during the perimenstrual period could be due to an elevation of estradiol, because estradiol does increase during the luteal phase and this could elevate BDNF.…”
Section: Epilepsymentioning
confidence: 99%
“…It is also possible, although less commonly discussed, that seizures that occur during the perimenstrual period could be due to an elevation of estradiol, because estradiol does increase during the luteal phase and this could elevate BDNF. Alternatively, and more widely accepted, is the view that waning progesterone at the time of menses leads to a disinhibition, and this lack of inhibition leads to increased seizure frequency [147].…”
Section: Epilepsymentioning
confidence: 99%
“…However, in addition to the finding that the HCs were less likely than the LCs to have complex partial seizures, it is also worth noting that there was a trend for greater proportion of women in the LC than HC group to report menstruation as a seizure precipitant ( 2 ‫ס‬ 2.91, df 1, p ‫ס‬ 0.088). Herzog et al (33), reviewing classifications of catamenial epilepsy, suggested that about a third of women with intractable complex partial seizures have seizures related to their menstrual cycle. It is possible that this biologic relationship between complex partial seizures and menstruation makes them seem less controllable.…”
Section: Discussionmentioning
confidence: 99%